2022
DOI: 10.1038/s41598-022-24853-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a diagnosis of sarcoidosis among US veterans of Iraq and Afghanistan

Abstract: This study evaluated risk factors of sarcoidosis among Airborne Hazards and Open Burn Pit Registry (AHOBPR) participants using a retrospective age and sex-matched case–control design of AHOBPR participants deployed to Afghanistan or Southwest Asia with and without sarcoidosis diagnosed in the Veterans Health Administration (VHA). Logistic regression models tested for associations between sarcoidosis and self-reported cumulative deployment-related exposures. 661 Veterans (0.37%) were diagnosed with sarcoidosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Results from the questionnaire identified that only veterans exposed to convoy activity had a statistically significant (odds ratio, 1.16; 95% CI, 1.00-1.35; P=.046) increased risk for developing sarcoidosis. 17 Interestingly, enlisted personnel had a higher rate of sarcoidosis than officers, comprising upwards of 78% of cases in the Military Health System from 2004 to 2013. 9 This finding requires further study, but increased exposure to toxins due to occupational specialty may be the cause.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
“…Results from the questionnaire identified that only veterans exposed to convoy activity had a statistically significant (odds ratio, 1.16; 95% CI, 1.00-1.35; P=.046) increased risk for developing sarcoidosis. 17 Interestingly, enlisted personnel had a higher rate of sarcoidosis than officers, comprising upwards of 78% of cases in the Military Health System from 2004 to 2013. 9 This finding requires further study, but increased exposure to toxins due to occupational specialty may be the cause.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
“…Increased measurements of metal elements have subsequently been found in the plasma of veterans with pulmonary sarcoidosis compared with controls ( 5 ). In veterans registered in the Airborne Hazards and Open Burn Pit Registry who were deployed to Afghanistan or Southwest Asia, self-reported cumulative exposure to convoy activities involving vehicle operations was the only exposure that reached significance for increased sarcoidosis risk in adjusted analysis ( 6 ). In 2022, the association of burn pit exposure and sarcoidosis was recognized on a legislative level with the passage of the Honoring Our PACT (Promise to Address Comprehensive Toxics) Act through the U.S. Congress.…”
mentioning
confidence: 99%